Merging the views: highlights on the fusion of surface and subsurface geodata and their potentials for digital geoarchaeology - Siart, Christoph (Digital geoarchaeology, 2018)
A multi-method research design based on geophysical prospecting (electrical resistivity tomography, seismic refraction), DEM generation (terrestrial LiDAR and total station) and GIS is applied for the first time to investigate geoarchaeologically relevant sites in an integrated way. Fusing multi-resolution surface and subsurface geodata provides profound insights into the formation, geometry and geomorphologic processes of karst depressions which serve as geoarchives in the Mediterranean area. Case studies from different locations on Crete are provided. In order to define crucial methodological requirements and guidelines for data fusion, both the impact of different elevation models and different geophysical methods and the influence of data resolution are assessed. Different approaches are presented along with their advantages and shortcomings, highlighting the various options offered by combining surface and subsurface geodata.